Questions about Paul's Gospel of Justification - Newman, Paul W. (Journal of ecumenical studies, 2020)
The Pauline gospel of justification is a major factor in current ecumenical discussions between Catholic and Protestant churches. The doctrine needs to be tested by the life and teachings of Jesus, who was centered on the Reign of God. Issues challenging justification by means of retributive justice are the doctrine of return that is central to the prophetic tradition, the emphasis of Jesus on the bilateral covenantal law of love for neighbors and enemies, the discrediting of death penalties in the world, the widespread emulation of Jesus' compassion, the inability of many modern people to believe in a scapegoat logic of forgiveness, and the desperate need of the world for the gospel of the Reigning of God.